Regularidade global Gevrey das soluções de certas classes de operadores parciais lineares de primeira ordem - Coelho, Laurencie Salles (Universidade Federal de São Carlos, 2004)
In this work we study global Gevrey hypoellipticity on the Euclidean 2-space R² for a class of first order linear partial differential operators with coeffcients in Cw2χ (R). Necessary and suffcient conditions for global Gevrey hypoellipticity are proposed.
Keywords: Séries de Fourier; Funções Gevrey periódicas; Ultradistribuições Gevrey periódicas; Regularidade global Gevrey; CIENCIAS EXATAS E DA TERRA::MATEMATICA